If it's not what You are looking for type in the equation solver your own equation and let us solve it.
17=n/11
We move all terms to the left:
17-(n/11)=0
We add all the numbers together, and all the variables
-(+n/11)+17=0
We get rid of parentheses
-n/11+17=0
We multiply all the terms by the denominator
-n+17*11=0
We add all the numbers together, and all the variables
-1n+187=0
We move all terms containing n to the left, all other terms to the right
-n=-187
n=-187/-1
n=+187
| -2(q–5)+-3=-5 | | p=-23 | | -3x+4x=-4 | | -340=-17x | | c/4+1/9=-8/9 | | b/14=-9 | | 14=-5x-2x | | x^2+18x+25=4x+1 | | 13=m/13 | | (y—5)6+13–5y=7 | | 5v+2v=-7 | | 113=m/13 | | 2a+6a=8 | | -5g-20-20=-8g+11 | | (5y5)=(5y) | | 34=19+p | | -24=x-1 | | -18=-6x+3x | | 7(x+11)=9x-5 | | -23+x=7 | | -2=-4k+3k | | -216=24n | | 3y=-9-12 | | -11+x=-14 | | x^2+2x+6=8x+1 | | 2r^2+6r-56=0 | | 3(2b-1)=-21+5b | | 1=v-3-1 | | 9+m=-8m | | 10m=-70 | | (80+x)(1.4)=80(0.5)+0.9x | | 2x-5(x-4)=-2+4x+1 |